Thin calcium-phosphate coatings produced by RF Magnetron sputtering and prospects for their use in biomedical engineering; Biomedical Engineering; Vol. 42, iss. 3 - Aronov A. M.; Pichugin V. F. Vladimir Fyodorovich; Eshenko E. V.; Ryabtseva M. A.; Surmenev R. A. Roman Anatolievich; Tverdokhlebov S. I. Sergei Ivanovich; Shesterikov E. V. Evgeny Viktorovich (2008, 2008)
Title screen